Biological Applications of Organic Electrochemical Transistors: Electrochemical Biosensors and Electrophysiology Recording - Bai, Liming; Elósegui, Cristina García; Li, Weiqi; Yu, Ping; Fei, Junjie; Mao, Lanqun (Frontiers in Chemistry, 2019)
Organic electrochemical transistors (OECTs) are recently developed high-efficient transducers not only for electrochemical biosensor but also for cell electrophysiological recording due to the separation of gate electrode from the transistor device. The efficient integration of OECTs with electrochemical gate electrode make the as-prepared sensors with improved performance, such as sensitivity, limit of detection and selectivity. We herein reviewed the recent progress of OECTs-based biosensors and cell electrophysiology recording, mainly focusing on the principle and chemical design of gate electrode and the channel. First, the configuration, work principle, semiconductor polymer of OECT was briefly introduced. Then different kinds of sensing modes were reviewed, especially for the biosensing and electrophysiological recording. Finally, the challenges and opportunities of this research field are discussed.